Pappasang dalam Komunikasi Budaya Masyarakat Lokal Suku Mandar - Ridwan, Ahmad Rifai; Rustan, Ahmad Sultra; Nurkidam, A (Palita: Journal of Social Religion Research, 2022)
This study aims to determine the meaning of Pappasang in the cultural communication of the local Mandar tribe and to find out the value of the local community pappasang in the artistic touch of the Mandar tribe. The research method uses a descriptive qualitative approach. The number of informants was three people were selected using a purposive sampling technique. Data were obtained from questions to the informants, then analyzed and then made an abstraction of all the results of the interviews. The study results show that Pappasang has various meanings, such as Pap Pairs Puang_Allah Ta-Ala, Pappasang To Mawuwen, Paissangan, Pattirioloang and Pepasang, depending on the need. Pappasang of local communities in the Cultural Communication of the Mandar tribe, there is a determination of behaviour and values. Two Pap Pairs, first, determine the various types of Pap Pairs before the research is done. The value of Pap Pairs in the Kakkangan community pays attention to the criteria for exposure to information obtained from the Kakkangan community, which is the reference material for the emergence of the Pap Pair idea as cultural communication.